THE EFFECT OF POSITRONIUM FORMATION IN E(+)-LI AND E(+)-NA SCATTERING - Adhikari, S. K.; Ghosh, A. S.; Ray, H. (Elsevier B.V., 1994)
We studied e+-Li and e+-Na scattering using the close-coupling approximation in the static and coupled static expansion schemes. The effect of the positronium formation on the elastic channel is found to be strong in both cases. In the case of the lithium atom the effect is dramatic; the inclusion of the positronium formation channel transforms the purely repulsive effective e+-Li S wave (static) potential to a predominantly attractive (coupled static) potential. In this case, in the static model delta(0)-delta(infinity) = 0, whereas in the coupled static model delta(0)-delta(infinity)=pi. According to Levinson's theorem this suggests the presence of a S wave bound or continuum bound state in the e+-Li system.